Navia yariensis (Bromeliaceae) a new narrow leaved species from Caquetá, Colombia - Gouda, Eric J. (Phytotaxa, 2026)
A new Navia species is described and illustrated here and compared with the morphologically closest species in the genus, and some other similar ones from Colombia.